The Effect of Training Models Using Modified Goals and Pyongyo on Dollyo Chagi Kick Skills in Taekwondo Athletes - Rizky, Oddie Barnanda; Raibowo, Septian; Ilahi, Bogy Restu; Permadi, Andes; Prabowo, Andika Restu (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objectives. This study seeks to evaluate the impact of Dollyo Chagi training utilising modified goalposts and pyongyo on the kicking proficiency of Taekwondo competitors. Materials and Methods. This study employs an experimental research design with a Pretest-Posttest Control Group methodology. The data for this study were derived from the Dollyo Chagi kicking skills assessment, which was administered twice: a pretest prior to the training intervention utilising modified goalposts and pyongyo, and a posttest following the training with the same modifications. Results. The calculations of the pretest and posttest data revealed an increase in the average posttest score, rising from 16.9 to 27. The mean difference is calculated to be 10.1. The increase, when stated as a percentage relative to the pretest mean of 16.9, was 59.77%. Conclusion . The conclusion drawn is that H0 is not rejected and Ha is accepted, indicating an effect of dollyo chagi kick training utilising modified goals and pyongyo on dollyo chagi kick skills at the Rafflesia Taekwondo Club in Bengkulu City